Human resources development in Salatiga city education department (analysis of work discipline and work motivation on performance mediated by education and job training of employees) - Samtono Samtono; Tri Maryani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this research is to analyze and explain the effect of work discipline, work motivation, education and training on performance. analyze and explain whether education and training mediate work discipline and motivation on the performance of Salatiga City Education Office employees. The approach in the research here is a quantitative inferential type approach. The sampling technique used was the census technique, meaning that all members of the population were taken as samples, while the total sample was taken as many as 89 subjects, while the data collection technique used a questionnaire technique with a Likert scale of 5 options, while data analysis was carried out using multiple regression analysis, as well as testing mediation/path analysis is used to determine the direct or indirect effect of the independent variables on the dependent variable. The research results obtained the following results: 1. There is a positive and significant influence of work discipline on education and training. 2. There is a positive and significant influence of work motivation on education and training. 3. There is a positive and significant influence of work discipline on employee performance, 4. There is a positive and significant influence of work motivation on employee performance 5. There is a positive and significant influence of education and training on employee performance. 6. Education and training do not mediate work discipline on employee performance. 7. Education and training do not mediate work motivation on employee performance.